Dynamic heterogeneity in homogeneous polymer melts. Issue 25 (10th June 2021) - Chu, Linlin; Xu, Kaipin; Graf, Robert; Yan, Zhi-Chao; Li, Junfang; Yao, Ye-Feng
Abstract : Unexpected dynamic heterogeneity in "homogeneous" PEO melts was disclosed by combined using 1 H Hahn echo nuclear magnetic resonance (NMR) and 1 H double-quantum (DQ) NMR. Abstract : Chain entanglement behaviors were studied by 1 H Hahn echo nuclear magnetic resonance (NMR) and 1 H double-quantum (DQ) NMR experiments. Poly(ethylene oxide) (PEO) was chosen to investigate the chain entanglement behaviors. The 1 H Hahn echo NMR results demonstrate that the critical molecular weight of PEO is approximately 6 kg mol −1 . Above this critical molecular weight, chain entanglements start to occur in the melts resulting in anisotropic motions of polymer chain. The 1 H DQ NMR observations establish that PEO melts with molecular weights above the critical value exhibit dynamical entanglements. The entangled networks, formed by PEO with a molecular weight of 480 kg mol −1 (PEO480), present slow mobility and rather homogeneously distributed chain entanglements, while the entangled networks, formed by PEO with a molecular weight of 255 kg mol −1 (PEO255), present fast mobility and obvious dynamic heterogeneity in the distribution of chain entanglement. Short chain PEOs like that with a molecular weight of 2 kg mol −1 are demonstrated to function like solvents when being added in an appropriate concentration to PEO480, and the dilution effect increases the chain mobility of PEO480. Moreover, properly diluted PEO480 networks exhibit dynamic heterogeneity similar to that observed in PEO255.